EKSTRAK JAHE DAN KOMBINASI EKSTRAK JAHE DENGAN NERVE GLIDING EXERCISE UNTUK MENURUNKAN NYERI PERGELANGAN TANGAN - Fiastiningrum, Prit; Fitriana, Nurul Fatwati (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
Wrist pain is a condition where an individual experiences discomfort in the wrist, which both traumatic and non-traumatic factors can cause. Non-traumatic wrist pain often results from inflammation in the tissues around the carpal tunnel, leading to its narrowing. This condition is commonly seen in activities that involve prolonged and repetitive hand movements, such as in batik artisans. This study aimed to determine the effect of ginger extract and the combination of ginger extract with nerve gliding exercise on wrist pain in batik artisans in Papringan Village, Banyumas. This study employed a pre-experimental design with a two-group pretest-posttest approach. The population consisted of batik artisans in Papringan Village, with a sample size of 20 individuals selected using a total sampling technique. Data analysis included both univariate and bivariate analyses. The study found a significant effect of ginger extract and the combination of ginger extract with nerve gliding exercise on reducing wrist pain. Wrist pain experienced a reduction and had a substantial effect, as evidenced by a high correlation coefficient.